Adaptive Seismic Upgrading of Isolated Bridges with C-Gapped Devices: Model Testing - Ristic, Jelena; Ristic, Danilo; Behrami, Ragip; Hristovski, Viktor (Civil Engineering Journal, 2024)
The seismic safety margins of seismically isolated bridges have not been thoroughly studied or comprehended due to a lack of actual on-site data observations. This study introduces a newly validated method for the efficient seismic protection of bridges that may be exposed to extremely strong, multidirectional near-source and critical far-source earthquakes. The isolated system was improved by incorporating innovative adaptive horizontal C-multigapped (HC-MG) energy dissipation devices to overcome the safety limitations associated with solely using isolated bridges under seismic loads. The newly developed adaptive C-gapped (ACG) bridge system was systematically validated through extensive experimental seismic tests on bridge models and additional analytical studies. The new ACG bridge system represents an advanced technical solution that integrates the benefits of seismic isolation and energy dissipation. The seismic isolation system for the large-scale ACG bridge prototype was designed using double spherical rolling seismic bearings (DSRSB). The seismic performance of the system was enhanced with adaptive HC-MG energy dissipation devices. The improved seismic performance of the system was demonstrated through extensive seismic shaking-table tests on the ACG bridge prototype, simulating selected seismic inputs characteristic of typical near- and far-source earthquakes. Doi: 10.28991/CEJ-2024-010-09-01 Full Text: PDF